Employee Development at the Manpower and Transmigration Office of Sumedang Regency - Edi Setiawan; Dewi Siti Julaeha (Universitas Medan Area, 2020)
This paper aims at obtaining the objective data and information regarding to employee development, the obstacles in employee development and efforts to overcome obstacles to employee development at the Manpower and Transmigration Office of Sumedang Regency. The method used was descriptive qualitative with four research informants, namely the Office Secretary, the Head of General Affairs, Asset and Personnel, the Head of the Finance Subdivision and the Head of the Training Institutional Development Division. Data collection techniques through secondary data collection was such as literature study, primary data collection techniques were such as observation, interviews and documentation that were then analyzed by steps in the form of data reduction, data presentation, verification and triangulation. The results obtained indicated that the development of employees at the Manpower and Transmigration Office of Sumedang Regency was still not perfect and not in accordance with the objectives of the development itself. The changes in employee needs due to limited human resources, changes in organizational needs and changes in the organizational environment required the Manpower and Transmigration Office of Sumedang Regency to make efforts by optimizing development costs, minimizing changes in employee needs, minimizing changes in organizational needs and minimizing changes in environmental needs.